Implementasi Rencana Kerja Pemerintah Gampong Sesuai Pemendagri No 114 Tahun 2014 Kabupaten Aceh Barat - Nur Annisah, Fanny; Safrida, Safrida (CV RIFAINSTITUT, 2022)
This article aims to understand how to evaluate the gampong annual development plan in formulating development strategies and policies as well as formulating the Gampong Government Work Plan program for 1 (one) year. The problem is focused on the obstacles that occur during the preparation of the work plan activities of the gampong government by the DPMG agency and the gampong apparatus. In order to approach this problem, a descriptive qualitative method is used as a reference. The data were collected through Interview, Observation, Documentation. This study concludes that in carrying out the work plan activities of the gampong government in accordance with the Ministry of Home Affairs No. 114 of 2014 that in order to achieve national development priorities and targets, annual planning synergies are needed between the central government and regional governments as well as between regional governments. Then analyze the process of achieving the maximum implementation of gampong development programs/activities and are easily identified which refers to the Minister of Home Affairs Regulation No. 114 of 2014.